Eurycoma Longifolia jack hydrogel improves the quality of healed wounds - Faisal, Ghasak Ghazi; Abd Fuaat, Azliana; Ahmad Affandi, Khairunisa; Riyadh Al-Bayati, Maryam (2022)
Background: Wound healing is a complicated process of a strictly regulated mechanism which will restore the tissue back to near normal structure. However, healed wounds tend to be weaker than normal tissue and that is why methods are searched to improve the strength and thickness of the healed tissue. Eurycoma longifolia jack (EL) root extract is known for its potent antimicrobial and anti-inflammatory properties. This study aims to investigate the effects of EL hydrogel on the quality of healed wound in terms of epidermal/ dermal thickness and the amount of collagen formed. Methods: EL roots were extracted and formulated into a hydrogel using appropriate dosing according to the extract IC50 on fibroblasts. Twenty Sprague Dawley rats were divided into 4 groups (n=5); untreated (-ve) control, Hydrocyn® aqua gel (+ve) control, vehicle (xanthan) and TA hydrogel groups. A full-thickness circular excisional wound (15×15) mm was created on the rat’s back. The treatment was applied for 21 days. The healed wound was harvested and processed into slides to determine the healed skin epidermal/dermal thickness and examination of collagen fibre orientation. Results: TA hydrogel treated group had the highest epidermal thickness among the other groups. Dermal thickness was significantly higher in EL group than the vehicle (xanthan) hydrogel group. The collagen fibres in TA hydrogel group were oriented in a mixed pattern. Conclusion: EL hydrogel improved the quality of the healed wound compared to other test groups which indicates that this extract has a strong potential to be used as a wound healing agent.